MicroRNA dysregulation and multi-targeted therapy for cancer treatment. (January 2020) - Balatti, Veronica; Croce, Carlo M.
Abstract: We established that loss of miR-15a/16–1 genes on chromosome 13q14 is the most common alteration in Chronic Lymphocytic Leukemia (CLL) and that miR-15/16 are crucial negative regulator of BCL-2, an antiapoptotic gene overexpressed in most CLLs and in many other malignancies. We have also shown that miR-15/16 target ROR1, a cell surface receptor for Wnt5a which can enhance growth/survival of CLL cells. Interestingly, ROR1 is expressed by many cancers, but not by normal adult tissues. Moreover, Venetoclax, the anti-Bcl- 2 drug, and Cirmtuzumab, the monoclonal antibody against ROR1, are synergistic in killing CLL cells. Since an additional miR-15/16 locus exists on chromosome 3q25 ( miR-15b/16–2 ), we generated a knocked out mouse model to study its the role in cancer. We observed that the KO mice developed predominantly CLL. Thus, we generated a double knock out mouse model where both miR-15/16 loci were deleted. Surprisingly we observed that 77% of double KO mice developed Acute Myeloid Leukemia (AML). Based on these evidences, we anticipate that also AMLs with low miR-15/16 expression, overexpression of BCL2 and expression of ROR1, would show an excellent response to a combination therapy with Venetoclax and Cirmtuzumab, since both drugs target the same malignant cells that have lost miR-15/16.